Sincerity in Asma Nadia’s Novel Surga Yang Tak Dirindukan 2 - Putri, M (KnE Social Sciences, 2018)
The purpose of this study is to analyze and describe sincerity in novel created by Asma Nadia by using Psychology Individual theory of sincerity reflected in the struggle that fulfills Arini’s struggle and patience in reaching the goal. The main character of Arini can be described through the Psychology Individual theory of Alfred Adler (2010). Fulfillment psychology individual theory is indicated by her motifs, her sincerity, her struggle against her illness, her weakness, her patient sacrifice to let her husband marry with woman. Her family is complete and happy even without Arini, and Arini is happy because finally she is successful to unite her husband and his lover. The study is conducted by descriptive qualitative method. The findings show that Arini is a great woman, having completed her duty as a real wife and she is able to overcome all her difficulties through her sincerity and she has also shown great responsibility in all things. Keywords: sincerity, love, responsibility.